2017
DOI: 10.1007/s00231-017-2069-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of the lattice Boltzmann method for simulation of the mold filling process in the casting industry

Abstract: The aim of this work is the development of the lattice Boltzmann model for simulation of the mold filling process. The authors present a simplified approach to the modeling of liquid metal-gas flows with particular emphasis on the interactions between these phases. The boundary condition for momentum transfer of the moving free surface to the gaseous phase is shown. Simultaneously, the method for modeling influence of gas back pressure on a position and shape of the interfacial boundary is explained in details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…From practical point of view, the LBM1 algorithm discussed here should be useful in applications where the original BGK Lattice Boltzmann was combined with the relaxation time τ = 1. For example, in [33,12,6,28,17,13,9,34,25,3,10,14,15,22] it is possible to save more than 75% of the memory by using LBM1 described here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From practical point of view, the LBM1 algorithm discussed here should be useful in applications where the original BGK Lattice Boltzmann was combined with the relaxation time τ = 1. For example, in [33,12,6,28,17,13,9,34,25,3,10,14,15,22] it is possible to save more than 75% of the memory by using LBM1 described here.…”
Section: Discussionmentioning
confidence: 99%
“…In the standard LBM BGK algorithm the relaxation time τ may range from nearly 1/2 up to 1 (highly viscous flows), however, the choice τ = 1 is a popular choice for single relaxation time BGK approximation [33,20,12]. For example, τ = 1 was chosen in the gray LBM model used for porous media flows [6], to compute first predictor step and fictitious viscosity solution in the simulation of the mold filling process [28], in the LBM multicomponent flow simulation with comparison to Finite Volume Methods [21], the immersed-boundary LBM for particles suspended in fluids [17]. It was shown that the value of τ influences the accuracy of the LBM solver in flow through narrow pores and τ = 1 case was in the best agreement with advanced multi-relaxation time schemes [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…The liquid could fill them freely, and the air surrounding the system was considered by the atmospheric pressure exerted on the free surface. This approach is often used in modeling foundry and metallurgical processes [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…This decreases its computational demands. Although twophase flow LBM models of the casting processes exist, Szucki et al (2017), Kharmiani and Passandideh-Fard (2018), a single phase model with free-surface boundary, Ginzburg and Steiner (2003), Zhang et al (2019), is considered within this work in order to keep the computational simplicity and cost efficiency.…”
Section: Introductionmentioning
confidence: 99%